Sustainability as a dynamic organizational capability: a systematic review and a future agenda toward a sustainable transition - Amui, Lara Bartocci Liboni [UNESP]; Jabbour, Charbel Jose Chiappetta [UNESP]; de Sousa Jabbour, Ana Beatriz Lopes [UNESP]; Kannan, Devika (Elsevier, 2017)
Sustainability is a managerial trend that plays an important role in the contemporary organizational strategy. A company's capability to make sustainability more dynamic and integrated with strategies, transforming it into a business asset, has yet to be studied. This process of adaptation is reflected through innovative practices. However, there is still a gap between these practices and the organization's strategies and capabilities. The aim of this work was to conduct a systematic literature review of the dynamic capabilities for sustainability. Afterward, it was possible to systematize the available knowledge, assessing the current lack of research integrating both themes. The mainstream literature was classified and coded, resulting in a framework for what has been done to date, with recommendations to guide future research. Results show that more research is needed on dynamic capabilities for sustainability, especially in emerging economies in general. Future studies should also consider mixed methodologies and comparative perspectives in multiples sectors or in the services sector. There is also opportunity to discuss managerial innovations toward sustainability through research alliances between different institutions around the world. In short, there are few studies that connect both themes— corporate sustainability and dynamic capabilities—and for this reason there is an opportunity for future studies seeking to identify what kind of dynamic capabilities can be developed to more effectively overcome the emerging sustainability challenges.
Keywords: Dynamic capabilities; Dynamic capability; Literature review; Sustainability; Sustainable innovation